Comparing territorial and functional constituency representations in Hong Kong. Issue 3 (September 2019) - Jang, Jinhyeok
Much has been studied on political representation either in democratic countries or in competitive authoritarian regimes. However, few have attempted to compare across the two. This article fills this gap by comparing democratic and authoritarian representations within the same collective decision-making body: the Legislative Council of Hong Kong. The original data derives from 2465 parliamentary questions made by 243 legislators serving in the last four legislative sessions from 1998 through 2012. The empirical analysis shows that the type of election variable does not have an impact on the volume of parliamentary questions but that it has a strong effect on the composition of parliamentary policy issues.